Children’s immunologic response from COVID-19: Clinical condition anda symptomatology (Research, Society and Development, 2023)
With the emergence of SARS-CoV-2, a respiratory syndrom has manifested in mass population, but they believe that it didn’t cause syntoms or complications for children, however in 2020, The United Kingdom issued an alert note about a condition very similiar to the one presented in adults. Facing it, some other countries started to notify similar cases and the Pedriaric Inflammatory Multisystem Syndrome (PIMS) was discovered, a complication observed in children who was infected by the COVID-19 virus. This Project is aimed to condense the main informations about the envolved mechanisms, from the narrative reviews using na eletronic data base. In its pathophysiology, an inflammatory cytokines storm is observed that occurs after the entrance of the vírus in the host cells from angiotensin-converting enzyme 2, that after will bring syntoms and determined its severity. Related to clinic condition, the most reported symptom is high fever, that could be associated to another signs, which can develop and cause complications. About the diagnosis, firstly, a very precise clinic analisys must be performed, followed by laboratory tests, in addition to associating imaging exams. Lastly, there isn’t a defined treatment protocol yet, being carried out in an individualized way, aiming each patient support, besides of therapeutic measures to reduce inflammation and restore organic functions. In conclusion, due to the reduction of cases there are less and less studies leaving many gaps about the disease.